Avolition-Apathy and White Matter Connectivity in Schizophrenia: Reduced Fractional Anisotropy Between Amygdala and Insular Cortex. (January 2018) - Amodio, Antonella; Quarantelli, Mario; Mucci, Armida; Prinster, Anna; Soricelli, Andrea; Vignapiano, Annarita; Giordano, Giulia Maria; Merlotti, Eleonora; Nicita, Alessia; Galderisi, Silvana
The avolition/apathy domain of negative symptoms includes motivation- and pleasure-related impairments. In people with schizophrenia, structural and functional abnormalities were reported in key regions within the motivational reward system, including ventral-tegmental area (VTA), striatum (especially at the level of the nucleus accumbens, NAcc), orbitofrontal cortex (OFC), as well as amygdala (Amy) and insular cortex (IC). However, the association of the reported abnormalities with avoliton-apathy is still controversial. In the present study, we investigated white matter connectivity patterns within these regions, using a probabilistic analysis of diffusion tensor imaging (DTI) data, in male subjects with schizophrenia. Thirty-five male subjects with schizophrenia (SCZ) and 17 male healthy controls (HC) matched for age, underwent DTI. SCZ were evaluated using the Schedule for Deficit Syndrome (SDS), the Positive and Negative Syndrome Scale (PANSS), and the MATRICS Consensus Cognitive Battery (MCCB). Probabilistic tractography was applied to investigate pathways connecting the Amy and the NAcc with the OFC and IC. Reduced fractional anisotropy (FA) was observed in left Amy–ventral anterior IC connections, in SCZ compared with controls. This abnormality was negatively correlated with avolition/apathy but not with expressive deficit scores. SCZ showed also a reduced connectivity index between right NAcc and medial OFC, as compared with controls. Finally, the left NAcc-dorsal anterior IC connectivity index was negatively correlated with working memory scores. Our results indicate that only the avolition/apathy domain of negative symptoms is related to abnormal connectivity in the motivation-related circuits. The findings also demonstrate that distinct alterations underlie cognitive impairment and avolition/apathy.